Developing Pop up Book Media on Solar System Material to Improve the Understanding of Grade VI Students at SD Muhammadiyah 1 Padas - Pratiwi, Syal Sabbilla; Nafi’an, Muhammad Ilman; Rofiah, Tutik Dinur (Indonesian Journal of Multidisciplinary Educational Research, 2023)
This study aims to develop a Pop up book to improve student understanding and identify the eligibility of Pop up book being developed to improve student understanding. This type of research method is Research and Development (R&D). The development model used is the ADDIE model, the data collection used is documentation, questionnaires, and tests. The result of the eligibility data analysis shows that the Pop up book is eligible to be used with the percentage of eligibility by media expert at 50% in revision 1, 73.3% in revision 2, and 93.3% in revision 3, eligibility by material expert of 91 .7%, and eligibility by pretest posttest experts of 80%. The increasing of understanding using Pop up book media can be seen from the analysis of the pretest and posttest data by comparing the average values obtained. The pretest value data before learning using the Pop up book shows an average result of 70. Meanwhile, the posttest value after learning using the Pop up book shows an average result of 83.28.